Violência no Brasil: os perfis ocultos de encarcerados e vítimas de mortes violentas - LIEBL, Caroline (2018)
Brazil is among the four largest prison populations in the world, and more violent deaths occur in its territory than in places with declared civil wars. In this context, based on the theme of violence, understood in its multiple forms of manifestations, the profiles of prisoners and victims of violent deaths in Brazil are a relevant object of study. The variables chosen for analysis of such profiles are age, race, gender and education level, and the temporal cut covers the years 2002 to 2016. The main data source of characteristics of violent deaths victims is the Mortality Information Subsystem, and the prisoners data source are InfoPen Reports and Maps of Violence, and it is done a comparative study between the collected data, in addition to bibliographic and documentary research. Adopting Pierre Bourdieu's reflexive methodology, it is objectified to analyze these profiles and to verify if there is equivalence between them, to discuss vulnerabilities reasons according to the variables, to demonstrate if there is a covert selectivity, and to discuss the various forms of violence that permeate the study object, as well as the portion of violence legitimized to the State in the punitive context. From the obtained results, it is observed that the majority profile of both prisoners and victims of violent deaths is equivalent and consists of men, black people, young people, with low schooling, reflecting the male performative socialization with expectations of violent habitus, the inheritance of slavery and racism in Brazil, the difficulty of achieving a high level of schooling in a community divided by great differentiation strata and distance between them, and the obstacles to which young people are submitted due to the insufficiency of own capitals to obtain better positions in the fields and effectively structure them. As observed, these groups are more vulnerable to physical, structural and symbolic violence and are affected by the penal system selectivity, which leads to conclude for a legitimacy crisis of punitive power exercise.